2021
DOI: 10.1002/cam4.4487
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐relatedlncRNAs can predict the prognosis of acute myeloid leukemia

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Subsequent stratification analysis demonstrated that IRL‐score could be applied to different clinicopathological subgroups and maintained its predictive power, with the exception of senior patients >65 years old. Finally, IRL‐score was able to predict prognosis independently of blast count and ELN risk stratification system, further demonstrating the prognostic potential of lncRNA signature in AML (R. Li et al, 2022 ). Comparably, Liu et al recently identified a prognostic 7‐lncRNA signature for AML which consisted of lncRNAs identified as highly expressed in AML in the TARGET dataset.…”
Section: Lncrna Function In Cancer and Amlmentioning
confidence: 81%
“…Subsequent stratification analysis demonstrated that IRL‐score could be applied to different clinicopathological subgroups and maintained its predictive power, with the exception of senior patients >65 years old. Finally, IRL‐score was able to predict prognosis independently of blast count and ELN risk stratification system, further demonstrating the prognostic potential of lncRNA signature in AML (R. Li et al, 2022 ). Comparably, Liu et al recently identified a prognostic 7‐lncRNA signature for AML which consisted of lncRNAs identified as highly expressed in AML in the TARGET dataset.…”
Section: Lncrna Function In Cancer and Amlmentioning
confidence: 81%
“…This means that incorporating lncRNA into preclinical models is essential for the discovery of prognostic biomarkers. Indeed, growing evidence has revealed that lncRNAs are intimately implicated in tumorigenesis, progression, prognosis, and drug resistance/sensitivity [ 15 ], and they are emerging as key regulators in the immune system, especially in inflammatory immune responses and immune-related pathways [ 16 ]. Although research on lncRNAs in AML is still in its infancy, evidence of their involvement as essential mediators and effectors of epigenetic changes has spurred epigenetics research [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs in the immune microenvironment are one of the most extensively studied kinds, regulating gene expression at the epigenetic, transcriptional, and post-transcriptional stages [ 15 ]. In AML, lncRNAs regulate the inflammatory immune response, B-cell activation, and vaccination response-related immunological pathways [ 16 ]. However, there is insufficient evidence for immune-related lncRNAs to predict AML prognosis and therapy, and their roles in the AML immune microenvironment has not received sufficient attention and warrant additional study.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on prognosis assessment in AML have mainly focused on a single gene or a group of genes related to specifc biological processes [4][5][6], instead of comprehensively integrating multiple pathways in AML expression gene sets. For example, autophagy-related signatures [7], ferroptosis-related genes [8], and immune-related signatures [9] were reported to be related to the prognosis of AML, respectively. Here, we applied gene set variation analysis (GSVA) to detect subtle changes in the pathway within an entire gene expression set [10], and then the patients were classifed according to the enrichment score (ES) of gene sets in an unsupervised manner.…”
Section: Introductionmentioning
confidence: 99%